Three-dimensional Imaging Reveals New Compartments and Structural Adaptations in Odontoblasts - Khatibi Shahidi, M; Krivanek, J; Kaukua, N; Ernfors, P; Hladik, L; Kostal, V; Masich, S; Hampl, A; Chubanov, V; Gudermann, T; Romanov, R A; Harkany, T; et al. (Journal of dental research, 2015)
In organized tissues, the precise geometry and the overall shape are critical for the specialized functions that the cells carry out. Odontoblasts are major matrix-producing cells of the tooth and have also been suggested to participate in sensory transmission. However, refined morphologic data on these important cells are limited, which hampers the analysis and understanding of their cellular functions. We took advantage of fluorescent color-coding genetic tracing to visualize and reconstruct in 3 dimensions single odontoblasts, pulp cells, and their assemblages. Our results show distinct structural features and compartments of odontoblasts at different stages of maturation, with regard to overall cellular shape, formation of the main process, orientation, and matrix deposition. We demonstrate previously unanticipated contacts between the processes of pulp cells and odontoblasts. All reported data are related to mouse incisor tooth. We also show that odontoblasts express TRPM5 and Piezo2 ion channels. Piezo2 is expressed ubiquitously, while TRPM5 is asymmetrically distributed with distinct localization to regions proximal to and within odontoblast processes.
Keywords: dentin; Odontoblasts; zubní dřeň; buněčné jádro; Dentin; Microscopy, Electron, Scanning; iontové kanály; myši transgenní; Ameloblasts; mikroskopie elektronová rastrovací; tvar buňky; kompartmentace buňky; řezáky; Dental Pulp; Mice; Mesenchymal Stem Cells; TRPM Cation Channels; kationtové kanály TRPM; Extracellular Matrix; mezenchymální kmenové buňky; buněčné výběžky; Cell Nucleus; Cell Shape; odontoblasty; zvířata; ameloblasty; Cell Surface Extensions; zobrazování trojrozměrné; Cell Compartmentation; myši; Imaging, Three-Dimensional; Mice, Transgenic; Fluorescent Antibody Technique; Ion Channels; Incisor; extracelulární matrix; fluorescenční protilátková technika; Animals